Nutrition and Food Supplies - Standing Joint Committee of Industrial Women's Organisations (London : The Labour Party)
1936-09 1936 1930s 33 pages : illustration NUTRITION AND FOOD SUPPLIES s. d. 1 copy 2½ post free 12 copies 1 6 100 copies 10 0 from THE LABOUR PARTY TRANSPORT HOUSE, SMITH SQUARE, LONDON, S.W.1. September, 1936. This Pamphlet was prepared by the Standing Joint Committee of Industrial Women’s Organisations, which is the Labour Party’s Advisory Committee on Women’s Questions, as a Report to the National Conference of Labour Women, Swansea, May, 1936, and was endorsed by that Conference. 127/NU/5/5/1/12